2012
DOI: 10.4103/0974-2727.98664
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Three Regimens of Treatment of Chronic Hepatitis B: Tenofovir, Entecavir and Combination of Lamivudine and Adefovir

Abstract: Background:Chronic hepatitis B is a disease of concern due to its life-threatening complications like cirrhosis, and hepatocellular carcinoma (HCC) in 20-40% of patients. There are about 400 million people affected worldwide with HBV, and over 300,000 die every year from HBV-related diseases. Oral antivirals like lamivudine, adefovir, entecavir, and tenofovir are commonly used to treat chronic hepatitis B. In this study, we tried to evaluate the comparative efficacy of these drugs alone and in combination.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Drug-resistant mutations reportedly develop in 7–16.4% (with 33% breakthrough). Combination of ADV + LAM 128 , 133 administered for 6–24 months was shown to result in rates of viral suppression of 42–53.3% and e seroconversion of 33–50%. Drug-resistant mutations occurred in only 7%, without any viral breakthrough.…”
Section: Drug Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Drug-resistant mutations reportedly develop in 7–16.4% (with 33% breakthrough). Combination of ADV + LAM 128 , 133 administered for 6–24 months was shown to result in rates of viral suppression of 42–53.3% and e seroconversion of 33–50%. Drug-resistant mutations occurred in only 7%, without any viral breakthrough.…”
Section: Drug Therapymentioning
confidence: 99%
“…ETV: 128 , 133 138 When administered for mean 6–36 months (maximum 5 years), ETV has resulted in viral suppression rates of 55–98%, and even higher rates were achieved with longer therapy duration (with e seroconversion in 18–56%). One study showed less response in genotype D, and another showed better response in e+ve cases; no drug resistance mutations were detected.…”
Section: Drug Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Since LAM plus ADV combination therapy was recommended for CHB patients in 2011, 25 a meta-analysis conducted in China showed that LAM plus ADV combination therapy can enhance anti-HBV agents and reduce viral resistance, which could permit long-term use. 17 In addition, a clinical study conducted in India suggested that LAM plus ADV combination therapy was not inferior to ETV and TDF monotherapies, especially when treatment costs were taken into consideration, 40 although this strategy remains controversial. A global multicenter, randomized and double-blind study found that LAM plus ADV combination therapy could not significantly suppress HBV DNA levels and reduce viral resistance, 41 and thus some treatment guidelines do not recommend this strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Combination nucleoside‐nucleotide therapy which can decrease the risk of the development of drug resistance is also recommended for the treatment of cirrhotic patients, but not naïve patients . Studies have shown that chronic hepatitis B is more prevalent among low socio‐economic groups, and most individuals in these groups cannot afford treatment due to the high cost of drugs such as ETV and TDF . For this reason, LAM plus ADV combination therapy, while not recommended by most guidelines as first line agents, may be reasonable treatment in groups that cannot afford the first line agents.…”
mentioning
confidence: 99%